Sonic Hedgehog Promotes Proliferation and Migration of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via Rho/ROCK Signaling - Zaiying Hu; Yingdi Chen; Shangling Zhu; Xiaoxue Feng; Baiyu Zhang; Jianlin Huang (Journal of Immunology Research)
Objective. To explore the underlying mechanism of the sonic hedgehog (Shh) signaling pathway in promoting cell proliferation and migration in fibroblast-like synoviocytes (FLS) from patients with rheumatoid arthritis (RA). Method. FLS were collected from 8 patients with RA and 3 patients with osteoarthritis (OA). The expression of smoothened (Smo, the Shh pathway activator) was quantified by real-time PCR and western blot. FLS were incubated with cyclopamine (a Smo antagonist), purmorphamine (a Smo agonist), Y27632 (a Rho/ROCK signaling inhibitor), or a combination of purmorphamine and Y27632, respectively. Cell proliferation was examined using cell counting kit-8 and cell cycle assays while cell migration was measured with Transwell and wound healing assays. Results. The expression of Smo was higher in FLS from RA patients than from OA patients (p<0.05). RA-FLS treated with purmorphamine showed significantly activated proliferation (119.69 vs. 100.0) and migration (252.38 vs. 178.57) compared to untreated cells (both p<0.001). RA-FLS incubated with cyclopamine or a combination of purmorphamine and Y27632 exhibited significant suppression of proliferation (81.55 vs. 100.0 and 85.84 vs. 100.0) and migration (100 vs. 178.57 and 109.52 vs. 185) ability (all p<0.001). Conclusion. Our results demonstrated that Shh promoted cell growth and migration of FLS in RA patients through the Rho/ROCK signaling pathway.